CAPTURING THE ONSET OF SNOWMELT IN HIGH ELEVATION POST-FIRE LANDSCAPES - MacDonald, Marin, author; Fassnacht, Steven, advisor; McGrath, Daniel, committee member; Tedesche, Molly, committee member (Colorado State University. Libraries, 2026)
In the Western United States, the increased threat of fire has impacted ecosystem health in high-elevation areas, as well as the associated water resources. Although fires have historically occurred in low-elevation forests adapted to fire conditions, in recent years, Colorado has experienced several high severity fires at higher elevations in areas critical to water storage. With much of the west relying on snow-dominated watersheds for water storage and availability, assessing the impacts of these fires on snowpack is critical.Although there has been recent research assessing snowpack trends in Colorado, remote sensing techniques using Sentinel-1 (S1) have had limited application. This study uses S1 Synthetic Aperture Radar (SAR) to detect the onset of snowmelt in high severity, high elevation sites in the Southern Rocky Mountains of Colorado and Southern Wyoming. Sites were compared to assess the interannual variability of the onset of snowmelt post-fire, and a multivariate regression was used to determine the effect of northness and elevation on the onset melt dates. Results were compared to SNOTEL station closest to each fire for comparing onset of melt dates in relation to peak SWE.